Good or bad: Application of RAAS inhibitors in COVID-19 patients with cardiovascular comorbidities (2020)
The coronavirus disease 2019 (COVID-19) pandemic is caused by a newly emerged coronavirus (CoV) called Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2). COVID-19 patients with cardiovascular disease (CVD) comorbidities have significantly increased morbidity and mortality. The use of angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor type 1 blockers (ARBs) improve CVD outcomes; however, there is concern that they may worsen the prognosis of CVD patients that become infected with SARS-CoV-2 because the virus uses the ACE2 receptor to bind to and subsequently infect host cells. Thus, some health care providers and media sources have questioned the continued use of ACE inhibitors and ARBs. In this brief review, we discuss the effect of ACE inhibitor-induced bradykinin on the cardiovascular system, on the renin–angiotensin–aldosterone system (RAAS) regulation in COVID-19 patients, and analyze recent clinical studies regarding patients treated with RAAS inhibitors. We propose that the application of RAAS inhibitors for COVID-19 patients with CVDs may be beneficial rather than harmful.